PELATIHAN DAKWAH BERBASIS BUDAYA LOKAL: MENGEMBANGKAN METODE KOMUNIKASI DAKWAH YANG KONTEKSTUAL BAGI PENYULUH AGAMA DI KOTA BAUBAU - Purnamayanti, Irma; Hanuddin, La; Salmawati Hada. N, Siti (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
The Association of Religious Instructors of Baubau City has a role in guiding the community to understand and practice religious teachings harmoniously. The implementation of this Community Service aims to develop contextual methods of da'wah communication through local culture-based da'wah training for religious instructors in Baubau City. This training is intended to equip instructors with more effective communication strategies, touch on local wisdom values, and are relevant to the social conditions of the local community. This study uses a qualitative approach with a case study method. Data were obtained through observation, in-depth interviews, and documentation of the training process and its application in da'wah activities. The results of the study showed that this training was able to increase awareness of instructors of the importance of a cultural approach in da'wah, as well as encourage the creation of da'wah communication methods that are more adaptive and accepted by the community. Religious instructors become more confident and creative in conveying religious messages.